Women explorers : perils, pistols, and petticoats - Cummins, Julie (Dial Books for Young Readers, 2012)
Profiles ten female explorers throughout history, describing the lives and accomplishments of Nellie Cashman, Annie Smith Peck, and other women who climbed mountains, studied Aboriginal cultures, lived with Pygmies, and more.